IRREGULARITIES EXISTING IN FIELD AREAS AND THE IMPORTANCE OF THEIR ELIMINATION - Guljamol Komilovna Saidova (Scientific Impulse, 2023)
Leveling of irrigated lands creates conditions for increasing the productivity of agricultural crops, preventing labor costs and excessive wastage of water during irrigation, high-quality processing between rows and high-quality harvesting by machines. As a result of several times tilling and watering the soil, unevenness of the field of various forms is formed, that is, long ridges and furrows are formed during plowing, high - low after watering, and residual unevenness from the previous year. In addition, in certain parts of the field, the soil settles and sinks due to repeated watering. It is recommended to eliminate such irregularities by current (exploitation) leveling.